Generasi Muda Kristen Unggul dalam Karakter melalui Kesehatan Mental - Esty Endaria Sembiring; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
In the next few years, Indonesia will reach the peak of the demographic bonus, where most of the population is of productive age and almost one-third are younger. The demographic bonus needs to be utilized optimally by improving the quality of its human resources. One indicator of the quality of human resources is mental health, which is believed to increase national productivity. Mental health plays a big role in realizing a superior generation. Through descriptive qualitative research methods, this study aims to discuss the superior character of the Christian youth that other young people do not have about mental health and Christian religiosity. The results showed that religiosity was directly proportional to better levels of mental health. The Bible through Christian Education has been shown to have a powerful influence on the mental health of individuals. Emotional intelligence developed through the ability to self-reflect, stress management, emotional release through forgiveness, peaceful conflict resolution, and increased optimism and hope are results that can be implemented in everyday life.